2018
DOI: 10.3390/ijms19102981
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Extracted from Oryza sativa L. Prevent Fluorouracil-Induced Nuclear Factor-κB Activation in Oral Mucositis: In Vitro and In Vivo Studies

Abstract: This study aims to investigate the immunomodulatory effect of anthocyanins (ANTs) from Oryza sativa L. extracts on 5-fluorouracil (5-FU)-induced oral mucositis, using a rat model and oral keratinocytes. ANTs were detected by high-performance liquid chromatography (HPLC)-electrospray ionization mass spectrometry. Animals were randomly given varying doses of ANT-rich extract treatment (500 mg/kg and 1000 mg/kg) in the absence or presence of 5-FU-induced mucositis. Buccal mucosae were photographed and scored for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
(67 reference statements)
1
17
1
Order By: Relevance
“…The total phenolic content was ~30 ± 1.5 mM gallic acid equivalent (gFW). Our results of the levels of C3G and the antioxidant properties of ANT extracted from O. sativa L. were lower than the levels in a previous study [26]. The differences in the C3G content and antioxidant capacity between the previous study and our findings probably stem from the diversity of rice cultivars, as well as the variety of extraction methods and analyses.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The total phenolic content was ~30 ± 1.5 mM gallic acid equivalent (gFW). Our results of the levels of C3G and the antioxidant properties of ANT extracted from O. sativa L. were lower than the levels in a previous study [26]. The differences in the C3G content and antioxidant capacity between the previous study and our findings probably stem from the diversity of rice cultivars, as well as the variety of extraction methods and analyses.…”
Section: Discussioncontrasting
confidence: 95%
“…Our investigation is in agreement with an in vivo study that demonstrated the anti-inflammatory role of ANT from Thai black rice using a 5-FU-induced oral mucositis model. This study indicated that ANT reduced the lesions induced by 5-FU in the oral mucosa via NF- κ B-mediated biological manipulations [26]. Furthermore, ANT suppressed the H 2 O 2 -induced IL-6 production and NF- κ B activation, which is in agreement with a previous study on normal human dermal fibroblasts exposed to UVB [62].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…9,10 Lastly, treatment of cells with anthocyanins, compounds with a similar action to NecroX-7, decreases HMGB1 release from cells and OM in mice treated with 5-FU. 11 Taken together with the report from Im et al, a model emerges in which OM results from epithelial cell death and release of pro-inflammatory proteins, such as HMGB1, from the dying cells.…”
Section: Answering the Questions Surrounding Hmgb1 Functionsmentioning
confidence: 77%
“…It includes articles that outline new approaches to reduce wound infection [1,2] as well as studies aimed at developing new in vitro chronic wound models as alternatives to animal experimentation [3]. The interest in natural products as potential wound agents is evidenced through three articles that investigated healing responses to honey [4], deoxyshikonin [5], and anthocyanins extacted from Oryza sativa L [6]. Understanding cytoskeletal interactions in keratinocytes and fibroblasts [7] as well as neutrophil proteome signatures [8] also provide important new information that may inform researchers with the development of new therapeutic approaches to improve healing responses.…”
mentioning
confidence: 99%